2007
DOI: 10.1038/sj.bmt.1705640
|View full text |Cite
|
Sign up to set email alerts
|

Ewing Sarcoma tumor cells express CD34: implications for autologous stem cell transplantation

Abstract: The significance of tumor cell contamination in marrow and peripheral blood stem cell (PBSC) collections of patients with solid tumors remains controversial. Various methods have been developed to purge tumor cells from autologous stem cell products, including CD34 þ selection. PBSC harvests from patients with Ewing family of tumors (EFT) were analyzed for contaminating tumor cells prior and after CD34 þ selection using reverse transcriptionpolymerase chain reaction (RT-PCR) and flow cytometry (FC) analyzes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
(38 reference statements)
1
2
1
Order By: Relevance
“…One group has reported that a subset of Ewing sarcoma cells may express CD34 [19]. In the current study, exclusion of CD34+ cells in our six-color panel did not eliminate the observed CD99+CD45- signal.…”
Section: Discussioncontrasting
confidence: 71%
“…One group has reported that a subset of Ewing sarcoma cells may express CD34 [19]. In the current study, exclusion of CD34+ cells in our six-color panel did not eliminate the observed CD99+CD45- signal.…”
Section: Discussioncontrasting
confidence: 71%
“…Hematopoietic cancer cell lines were reported to contain both, CD34 − and CD34 + subpopulations that were individually capable of generating tumor in NOD/LtSz‐scid/scid mice . This study demonstrated the presence of CD34 + subpopulation in several blood cancer cell lines, a feature that was earlier reported in several types of solid tumors . Compared to the CD34 − cell population CD34 + cells demonstrated higher rates of proliferation and capacity to generate colonies in methylcellulose based medium.…”
Section: Developmental Dynamics Of Cd34 On Cancer and Csc And Its Possupporting
confidence: 72%
“…46 CD34 has been reported to be negative on immunohistochemistry 27,44 but positive on RT-PCR. 48 Expression of p53 is seen in approximately 10% of ESFT and appears to be associated with an extremely poor outcome. 49 Cyclin D1 is often expressed and if negative, is associated with increased patient survival.…”
Section: Immunophenotypementioning
confidence: 99%